Di Blasio el piano de América - Di Blasio, Raúl, 1949-; Gabriel, Juán; Manzanero, Armando, 1935-; Muñíz, Marco Antonio, 1933- (BMG, 2002)
A collection of videos featuring Raul di Blasio playing various arrangements of popular songs.